Living in Change: The Role of Literature in the Preservation of Culture - Thomas B. Byers (Future Science, 2023)
I want to thank the organizers of this conference, and especially my friend Dr. Eva Leiliyanti, for this invitation to discuss a topic that is both interestingly complex and close to my heart. Thanks to all of you who have signed on as well; I am sorry that we do not have the opportunity to meet in person, but I am nonetheless grateful for this virtual encounter. Later on, I will spend some time interrogating and even challenging the three keywords here: “literature,” “preservation,” and “culture,” and I’ll propose a role for literature beyond mere “preservation.” But first, let us explore a few touchstone texts for some of the time-honored ways of affirming literature’s role in preserving culture. That way, if you get nothing else from this talk, you’ll at least get to hear a few poems.